2018
DOI: 10.22219/jep.v16i1.8180
|View full text |Cite
|
Sign up to set email alerts
|

Human Development Index, Unemployment and Poverty in Papua Province, 2010-2015

Abstract: Papua Province is one of the poorest provinces in Indonesia. Some of the variables that affect health levels including Human Development Index (HDI) and unemployment rate. This research analyzes Human Development Index and unemployment rate to poverty level in districts/cities in Papua Province during 2010-2015. Research data used in this research is secondary data from Central Bureau of Statistics of district/city in Papua Province. The independent variables used are open unemployment rate and Development Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In Papua, students' low writing self-efficacy is related to the quality of education. Several prior surveys have revealed that Papua has the lowest ranking among all of Indonesia's provinces (Amalia, Nurpita, & Oktavia, 2018) related to the education infrastructures. Also contributing to a new concern is the discrepancy in educational quality between eastern and western Indonesia, which manifests in poor educational outcomes.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In Papua, students' low writing self-efficacy is related to the quality of education. Several prior surveys have revealed that Papua has the lowest ranking among all of Indonesia's provinces (Amalia, Nurpita, & Oktavia, 2018) related to the education infrastructures. Also contributing to a new concern is the discrepancy in educational quality between eastern and western Indonesia, which manifests in poor educational outcomes.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The human development index has a significant and negative effect on poverty, meaning that an increase in the index will reduce the number of poor people in West Papua. Amalia et. al.…”
Section: Variablesmentioning
confidence: 99%